Impact of Domestic Investment, Foreign Investment, Government Expenditures, and Labor on Gross Domestic Product (GDP) in North Sulawesi - J. Mailili, Jeremy; P. F. Rorong, Ita; F.D. Siwu, Hanly (PT FORMOSA CENDEKIA GLOBAL, 2024)
The influence of domestic investment, foreign capital, government spending and labor on gross regional domestic product in North Sulawesi province. This is a very important process in advancing the country's progress. This process involves many aspects, including changes in social structures, attitudes to life, and national institutions. The aim of this research is to analyze the influence of domestic investment, the influence of foreign investment, government spending and labor on GRDP in North Sulawesi Province. The data source used is secondary data for the 2011-2021 period. Data obtained from the North Sulawesi Province Central Statistics Agency (BPS), journals and research results. The research method used is quantitative research, with the analysis technique being multiple regression analysis. The research results obtained are that it has a positive and significant impact on GRDP.